Phenotype and Genotype Characteristics of Staphylococcus aureus Resistant to Methicillin/Oxacillin Carrying Gene mecC in the Czech Republic from 2002 to 2017 - Mališová, Lucia; Jakubů, Vladislav; Musílek, Martin; Kekláková, Jana; Žemličková, Helena (Microbial drug resistance (Larchmont, N.Y.), 2020)
The aim of this study was to detect and characterize isolates of methicillin-/oxacillin-resistant Staphylococcus aureus (MRSA) carrying gene mecC (MRSA/mecC) and occurring in the Czech Republic within the period from 2002 to 2017. Altogether, 18 from 3,472 isolates of MRSA were mecC positive (0.52%). The first detection of MRSA/mecC in the Czech Republic is dated to 2004. MRSA/mecC isolates were susceptible to almost all tested antibiotics with few exceptions. Resistances to erythromycin (n = 2), clindamycin (n = 1), trimethoprim-sulfamethoxazole (n = 1), and rifampicin (n = 1) were found in the collection. Multilocus sequence typing and spa typing revealed a genetic heterogeneity of MRSA/mecC strains: three CCs (130, 425, and 2361), five STs (1245, 130, 2361, 425, and a new ST5480), and eight spa types (t843, t978, t1048, t1535, t1736, t6104, t8842, and t17153), which were detected in the study, with the highest prevalence of CC130/t843 lineage (n = 8, 44%). Except for two strains, none from 18 examined isolates harbored genes encoding any of S. aureus toxins: enterotoxins a-u, exfoliative toxins A, B, and D, toxic shock syndrome toxin-1, and the Panton-Valentine leukocidin.
Keywords: multilokusová sekvenční typizace; Oxacillin; Anti-Bacterial Agents; methicilin rezistentní Staphylococcus aureus; spa typing; mikrobiální testy citlivosti; proteiny vázající penicilin; mecC; Genotype; bakteriální geny; polymerázová řetězová reakce; Czech Republic; antibakteriální látky; MLST; Česká republika; oxacilin; Multilocus Sequence Typing; Penicillin-Binding Proteins; Polymerase Chain Reaction; Microbial Sensitivity Tests; Genes, Bacterial; genotyp; Methicillin-Resistant Staphylococcus aureus; Staphylococcus aureus, MRSA